IDENTIFIKASI KEBUTUHAN PENANGANAN JALAN NASIONAL 2015-2019 DI PROVINSI SUMATERA SELATAN - Ardhiarini, Rizky; Mulyono, Agus Taufik (Teknisia, 2015)
Multi-criteria analysis combines road condition assessment score (IRI, SDI, road width, V/C ratio, traffic volume, vehicle speed, travel time) with importance level of the development of the area. The analysis resultedthe need of maintenance of national road in South Sumatera (2015-2019) more optimally, efficiently and effectively. The result are as follows : (1) in 2015, 95,86% of the  roads require routine maintenance and 4,14% require capacity improvement by widening the road to 7,0 meter; (2) among 2016 to 2019, 100,0% of the roads require routine maintenance without widening. The implementation of the maintenance does notaffect much to reduce travel time, although 100,0% of road has a width of more than 7,0 meter and about 90,37% of road has IRI less than 4,0 m/km. The condition is caused by there are no maintenance requirements concerning the improvement of the substandard geometric.